Republic of Armenia : Second Review Under the Extended Arrangement and Request for Waivers of Nonobservance and Rephasing; Press Release; Staff Report; Supplement; and Statement by the Executive Director for the Republic of Armenia. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2015)
This paper discusses Armenia's Second Review Under the Extended Arrangement and Request for Waivers of Nonobservance and Rephasing. Since late 2014, Armenia's economic performance has been affected by significantly weaker external conditions, as the slowdown of the Russian economy, the weakening of the ruble, lower metals prices, and the strengthening of the dollar have led to pressures on external receipts, particularly remittances. Performance under the program has come under strain. Three performance criteria (PCs) were missed both at end-December 2014 and end-June 2015. The authorities are requesting waivers of nonobservance for the missed June and continuous PCs. The IMF staff supports completion of the review.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet